Cittadinanza europea e cittadinanza nazionale. Luci e ombre di un rapporto difficile - Marchetti, Maria (SocietàMutamentoPolitica, 2016)
The relationship between European citizenship and national one is since the first formulation the main topic of the debate on its statute. At the present time, the short circuit between European citizenship and national one produces differentiated effects: the freedom that member States have to assess the criteria for the acquisition of citizenship produces a contrast between ‘citizens non-resident’ and ‘non-citizens resident’.